LAND CAPABILITY EVALUATION FOR CROP PRODUCTION USING REMOTE SENSING, GIS AND GEOSTATISTICS IN RIETFONTEIN, NORTH WEST PROVINCE OF SOUTH AFRICA - Kabanda, Tabaro (Geo UERJ, 2015)
DOI: 10.12957/geouerj.2015.15026 Land capability evaluation is important in arid and semi-arid environment as environmental resources need to be sustainably used. Land capability evaluation for agriculture assesses the land performance for a specific use of crop production. The objective of this research is to establish the potential role of remote sensing (RS) and GIS in spatial planning for arable agriculture in a communal land use setting of North West Province. The primary data were obtained from soil samples collected to 1 m depth and secondary information was acquired from the remotely sensed data (SPOT 5). The factors taken into consideration were soil texture, soil depth, clay fraction, pH and land use/land cover. Weighted overlay was used to combine all the parameters and produce a final capability map for sorghum and sunflower at Rietfontein farm. The results show that sorghum cultivation is suitable while sunflower is marginally suitable for cultivation. The study demonstrates that the farm can be categorized into spatially distributed agriculture potential zones based on the parameters. This study provides knowledge and encourages local communities to use land obtained through land reform sustainably and ensure food security in the country.